Platelet-to-lymphocyte and Neutrophil-to-lymphocyte Ratios Predict Target Vessel Restenosis after Infrainguinal Angioplasty with Stent Implantation - Lee, Silvia (J Clin Med, 2020)
Platelet-to-lymphocyte (PLR), neutrophil-to-lymphocyte (NLR) and lymphocyte-to-monocyte (LMR) ratios are associated with the occurrence of critical limb ischemia in peripheral artery disease (PAD). We therefore investigated whether PLR, NLR or LMR are linked to target vessel restenosis (TVR) following infrainguinal angioplasty and stenting. Moreover, we studied on-treatment platelet reactivity and neutrophil-platelet aggregate (NPA) formation as potential underlying mechanisms. Platelet, neutrophil, lymphocyte and monocyte counts were determined one day after angioplasty and stenting in 95 stable PAD patients. Platelet reactivity and NPA formation in response to protease-activated receptor−1 stimulation were measured by light transmission aggregometry (LTA) and flow cytometry, respectively. PLR and NLR were significantly higher in patients who subsequently developed TVR (both p < 0.05). In contrast, LMR did not differ significantly between patients without and with TVR (p = 0.28). A PLR ≥ 91 and NLR ≥2.75 were identified as the best thresholds to predict TVR, providing sensitivities of 87.5% and 81.3%, and specificities of 34.9% and 50.8%, respectively, and were therefore defined as high PLR and high NLR. TVR occurred significantly more often in patients with high PLR and high NLR than in those with lower ratios (both p < 0.05). Patients with high PLR and high NLR exhibited significantly increased on-treatment platelet aggregation compared to those with lower ratios, and patients with high PLR had higher levels of NPA formation (all p < 0.01). In conclusion, PLR and NLR predict TVR after infrainguinal angioplasty with stent implantation. Platelet activation and neutrophil-platelet interaction may be involved in the underlying pathomechanisms